Studies on Frequency Selective Surfaces for Wireless Communication Applications - Kaur, Komalpreet (My University, 2019)
Wireless communication technology has covered many progressive paths and has upgraded performance and proficiency in the communication environment in term of removal of unwanted signal from the desired ones. To overcome or minimize the problem of interference of the unwanted signals from nearby frequency bands microwave special filters have been proposed that are called frequency selective surfaces (FSS). FSS is an array of periodically arranged of metallic patches or apertures on the dielectric substrate that shows total reflection and transmission, respectively. However, the transmission response of the FSS structures is basically a function of frequency, angle-of-incidence (AOI) and polarization of the incoming waves. Their inherent features that results from their specific design make them a potential candidate to use as spatial filters in variety of microwave applications such as radomes and satellite communication. In addition to this, the miniaturization as well as angular and polarization stability of the structure are the potential issues. Thus the research work presented in this thesis is based on design and simulated miniaturized FSSs that are less sensitive to both angle of incident and mode of polarization. In addition to this, presented work also include the utilization of FSSs to enhance the gain of CPW fed MPA antenna. The research work starts with the design and simulation of a SSLFSS (Single Square Loop Frequency Selective Surfaces) structure that offers stop band properties for IEEE.802.11b (2.4 GHz) and a complementary unit cell of the proposed stop band unit cell that shows pass band properties for the same IEEE 802.11b band. Secondly a Fan shaped FSS structure for dual pass of S (1.44 GHz-4.64 GHz) and X (6.32 GHz-12.17 GHz) band is designed and a complimentary and optimized structure of pass band is designed that offers dual stop band transmission characteristics for S (2.06 GHz- 4.4 GHz) and X (7.93 GHz-12.45 GHz) bands respectively. Then the fractal FSS structure with ultra-wide stop band (3.48 GHz to 12.31 GHz) properties is designed that is placed behind the ultra-wide band CPW fed antenna (3.39 GHz to 12.98 GHz) to improve its gain by 2.5 dB approx. All the proposed FSS structures including CPW antenna design and simulated using CST microwave studio 2016. Two FFSs; one Fan shaped FSSs and second is complimentary of the Fan shaped FSSs are fabricated using photolithography process and tested using two horn antenna and VNA for transmission parameters. The measured results are quite matching with simulated ones, allowing the FSS prototype to be suitable to work as a special filters for satellite navigation, telecommunication, Aircraft surveillance, amateur radio, Bluetooth, Zig-Bee, communications satellites, microwave devices, mobile phones , WLAN, Wi-Fi etc.
ME Thesis
Keywords: Microwave Absorbers; Frequency selective surfaces; UWB; Improvement in MSA gain